Design of solar-powered forced ventilation system and energy-efficient thermal comfort operation of greenhouse. (2021) - Revathi, S.; Sivakumaran, N.; Radhakrishnan, T.K.
Abstract: This study focuses on design of energy-efficient forced ventilation scheme by exploitation of renewable energy in agricultural greenhouse facilities, which are available to and applicable in the farming industry. For a high productive greenhouse, thermal comfort operation is essential, which is ensured by an effective and efficient ventilating fan and pad system. The spatial temperature variations inside greenhouse are regulated through high ventilation rate. But it is contrasted by the energy consumption costs. The provision of ambient uniform indoor environmental quality for plants whilst achieving energy and cost efficient operation in agriculture buildings represents a multi variant problem. The experimental study is conducted in the greenhouse facility available at Centre of Excellence for Vegetables, Tamil Nadu, India and the iterative dynamic programming scheme is proposed to determine the optimal sequence of ventilation set points by considering the meteorological conditions which affect the environment inside the greenhouse. For instance, this multi speed ventilation approach trade-off between the low and high ventilation rates in order to compensate the thermal stratification and energy consumed by the forced ventilation system. Considering the endurance level of plant physiology, the set point blueprint is determined under the compatible control region which is helpful to trail less energy cost and to realize lower level climate control objectives of the overall environmental control greenhouse. Moreover, the energy required is realized by a photovoltaic system design to guarantee the essential and continuous self-sustained operation of the greenhouse. The performance of the system is monitored over a period of time and the system is able to provide favourable growth conditions under sustainable ecological environment principles for greenhouse agro-ecosystem. In addition to minimisation of temperature variation, it provides thermal stability and comfort by mitigating heat stress ascertained during cycling of existing single speed fan operation with 30.83% energy savings.